Effect of gender gap in education on district level GDP per capital of Nepal - Dahal, Madhav Prasad (Economic Journal of Development Issues, 2012)
Growth theories developed in the 1980s and 1990s incorporate education centered human capital to explain the cross-country and country specific variations in the per capita gross domestic product. This article examines the effect of gender inequality in education on the per capita GDP of the districts of Nepal. Gender inequality in education is more pronounced in less developed countries than in developed countries. Utilizing the data pertaining to the year 2001 taken from Nepal Human Development Report 2004 published by United Nations Development Program (UNDP) country office Nepal, we find that gender gap in education has obvious negative impact on district level GDP per capita of Nepal. This bears implication in policy formulation to minimize the gender disparity in education. DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7211 Economic Journal of Development Issues Vol.13 & 14 2011, pp.65-74